1998
DOI: 10.1086/520274
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Previous Aspergillosis on the Outcome of Bone Marrow Transplantation

Abstract: A retrospective analysis of 48 patients with documented or probable invasive aspergillosis (IA) prior to bone marrow transplantation (BMT) was conducted in 16 centers. Treatment of primary IA was medical in all 48 patients and surgical in 20; clinicoradiological resolution of IA occurred in 30 of 48 patients. Pretransplantation risk factors for relapse IA, total mortality, and IA-related mortality were analyzed by multivariate logistic regression with the following dichotomous risk factors: surgery as part of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
136
1
10

Year Published

2002
2002
2010
2010

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 173 publications
(154 citation statements)
references
References 14 publications
5
136
1
10
Order By: Relevance
“…The 32% breakthrough rate despite secondary prophylaxis in our study was in line with the rate observed in other series [10,11]. Overall mortality was 16%, with one-quarter of deaths being attributed to breakthrough IFD.…”
supporting
confidence: 92%
See 2 more Smart Citations
“…The 32% breakthrough rate despite secondary prophylaxis in our study was in line with the rate observed in other series [10,11]. Overall mortality was 16%, with one-quarter of deaths being attributed to breakthrough IFD.…”
supporting
confidence: 92%
“…However, these patients are at high risk of recurrent IFD, often with fatal outcome. The reported incidence rates of recurrent IFD range from 16% to 33% [9][10][11], and IFD-related mortality may be as high as 88% [10,12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study showed a relatively low rate of IFI-related mortality in comparison with earlier studies. [4][5][6][7][8][9] This should be dedicated to the high active secondary prophylaxis, for most of our patients (95.9%, 47/49) received broad-spectrum antifungal agents. [7][8][9] The low proportion (10.2%, 5/49) of proven cases of historical IFI may explain the difference between our results and the literature, which reflects the higher severity of infection in Days after transplantation Figure 1 Cumulative incidence of failure of prophylaxis in patients with versus without residual diseases before transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…The possibility of post-transplant relapse of earlier IFI is extremely high and it is associated with a very dismal outcome. [4][5][6] Information about the feasibility of HSCT in patients with a history of IFI is limited. Few studies have focused on the secondary prophylaxis of IFI during HSCT and information about efficacy is limited.…”
Section: Introductionmentioning
confidence: 99%